2016
DOI: 10.1080/17508487.2016.1186102
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberal versus social justice reforms in education policy and practice: discourses, politics and disability rights in education

Abstract: This article uses Critical Discourse Analysis in order to discuss the equity and social justice implications of an envisaged education reform agenda in Cyprus, as articulated by two consultation reports commissioned by the World Bank. The reports highlight, inter alia, the imperative to improve teaching and enhance accountability regimes with regard to students' learning. Selected extracts from these documents are analysed in order to highlight the absence of a social justice discourse in the rhetoric of educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 63 publications
0
35
0
6
Order By: Relevance
“…En adición, , las participantes en conocimiento que el entrenamiento de alumnos para la evaluación SIMCE significada estandarización, tenían que seguir los mandatos de los directivos quienes se encontraban con "la soga en el cuello" 7 ante los posibles castigos y sanciones derivadas del accountability con altas consecuencias introducido por la ley SEP (Falabella, 2014).Estas paradojas mencionadas, se producen debido a que en escenarios educativos como el chileno, en donde predominan las lógicas de rendición de cuentas, la predisposición de las políticas alienta a los actores escolares a producir este tipo discursos y prácticas, es decir, se legitima y predomina la rendición de cuentas por sobre la inclusión escolar o cualquier otra iniciativa pedagógica dirigida a brindar a los educandos una experiencia escolar más integral, sustantiva y holística (Liasidou & Symeou, 2018;Slee, 2013).…”
Section: Discussionunclassified
“…En adición, , las participantes en conocimiento que el entrenamiento de alumnos para la evaluación SIMCE significada estandarización, tenían que seguir los mandatos de los directivos quienes se encontraban con "la soga en el cuello" 7 ante los posibles castigos y sanciones derivadas del accountability con altas consecuencias introducido por la ley SEP (Falabella, 2014).Estas paradojas mencionadas, se producen debido a que en escenarios educativos como el chileno, en donde predominan las lógicas de rendición de cuentas, la predisposición de las políticas alienta a los actores escolares a producir este tipo discursos y prácticas, es decir, se legitima y predomina la rendición de cuentas por sobre la inclusión escolar o cualquier otra iniciativa pedagógica dirigida a brindar a los educandos una experiencia escolar más integral, sustantiva y holística (Liasidou & Symeou, 2018;Slee, 2013).…”
Section: Discussionunclassified
“…A form of symbolic violence occurs, in which humans who were viewed as being in a socially risky situation are now categorised as societal risks (Wacquant 2016;Beach and Sernhede 2011). Instead of anchoring the school-community partnership within the district, the officials at South School choose to collaborate with established associations and organisations (Liasidou and Symeou 2018;Ball and Olmedo 2013). The school-community partnership thus becomes a market where different actors offer their services to the district of Southfield (Ball 2007).…”
Section: Discussionmentioning
confidence: 99%
“…(Head teacher, South School) Thus, the school-community partnership was stimulating the creation of a market for companies and organisations to sell their services. Previous research has shown how this form of cooperation creates other forms of governance, in which the problem is constituted based on what the offered services provide an answer to (Liasidou and Symeou 2018;Ball and Olmedo 2013). As a result, the activities carried out within the partnership are limited to the range of offers.…”
Section: A Market For Social Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this reasoning, education, health and welfare policies are restructured according to the market (Rose, 1999), and the domain of freedom is construed and governed in terms of the entrepreneur-self operating in a free market (Rose, 1996;Simons & Masschelein, 2015). By focusing on these two rationalities, our interest is in how the change from social liberal 'governing through society' to neoliberal 'self-governing' is shaping and reshaping disability and LLL policies (see also Brine, 2006;Goodley, 2014;Liasidou & Symeou, 2018;Mitchell & Snyder, 2015;Volles, 2016).…”
Section: Governmentality Within Policy Discourses Of Disability and Lmentioning
confidence: 99%